Unidimensionalidade e invasão cultural das políticas públicas para o pequeno produtor: pensamento único no discurso do Projeto Paraná 12 Meses - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
This study is based on discourse analysis and aims to identify the one-dimensional Marcusian theory in the dissemination of ‘Paraná 12 Meses Project’s purpose. Such initiative was developed by the government of Paraná between the late 1990s and early 2000s which was thought for the care of small rural producers. We sought to observe any favorable bias to Neoliberalism and agribusiness and whether they had contradicted the beneficiary’s horizontality and role throughout the development of the project, which was proposed and disseminated in the narrative of documents, releases and news. To this end, texts published in state newspapers between 1998 and 2002 were analyzed. A qualitative research was carried out in printed newspapers from the three historical regions of the state of Paraná. We had also verified government releases and articles that dealt directly or indirectly with that matter. The base documents that presented and drove the investments were also investigated. The analysis focused on the way in which the proposals were presented and supported in the published narrative. It was oriented mainly in relation to the ideological political concepts in vogue at that time, such as market efficiency and globalization or the idea regarding the agrarian reform. Expressions such as peasants, small producers or family farmers could show the status of such characters, regarding the idea of how the beneficiaries’ development was expressed. The role of the agents involved was also verified, we wished to understand if the representation was on technicians, producers or political authorities. Discourse analysis showed that the narrative sought to attract small producers to the logic of industrial agribusiness, aimed at meeting the needs and requirements of the buying market. The discourse was affirmative regarding the attempt to show that without the farming multinationals’ technologies and their models of production, small-scale agriculture would not be viable. Thus, there was no emancipation of the rural man in the structure of Paraná 12 Meses, yet legitimization of the agro-industrial model responsible for the rural exodus observed in the 1970s and 1980s. Such relations would consolidate the land model present in Paraná since the colonial period, establishing the supremacy of great property over the peasant and a monoculture economic model.
Keywords: Paraná 12 Meses; Pequeno produtor; Unidimensionalidade; Paraná 12 Meses; Small producer; One-Dimensional Theory; CNPQ::CIENCIAS SOCIAIS APLICADAS